2022
DOI: 10.3390/antibiotics11040449
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease Treatment Drug PBT2 Breaks Intrinsic Polymyxin Resistance in Gram-Positive Bacteria

Abstract: Gram-positive bacteria do not produce lipopolysaccharide as a cell wall component. As such, the polymyxin class of antibiotics, which exert bactericidal activity against Gram-negative pathogens, are ineffective against Gram-positive bacteria. The safe-for-human-use hydroxyquinoline analog ionophore PBT2 has been previously shown to break polymyxin resistance in Gram-negative bacteria, independent of the lipopolysaccharide modification pathways that confer polymyxin resistance. Here, in combination with zinc, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The authors were unable to select for mutants resistant to PBT2 + zinc treatment [ 601 ]. PBT2 and zinc was also able to break intrinsic polymyxin resistance in MRSA and VRE in vitro as demonstrated by De Oliveira et al [ 603 ], highlighting the utility of PBT2 to reverse both intrinsic and acquired mechanisms of antibiotic resistance in bacteria. Other studies investigating the utility of using natural products [ 605 ], traditional medicines [ 606 ] and other existing non-antibiotic drugs [ 607 , 608 ] in reversing antibiotic resistance in S. aureus and/or enterococci have also been published.…”
Section: Alternative Treatment Options For Vancomycin Resistant Infec...mentioning
confidence: 87%
See 1 more Smart Citation
“…The authors were unable to select for mutants resistant to PBT2 + zinc treatment [ 601 ]. PBT2 and zinc was also able to break intrinsic polymyxin resistance in MRSA and VRE in vitro as demonstrated by De Oliveira et al [ 603 ], highlighting the utility of PBT2 to reverse both intrinsic and acquired mechanisms of antibiotic resistance in bacteria. Other studies investigating the utility of using natural products [ 605 ], traditional medicines [ 606 ] and other existing non-antibiotic drugs [ 607 , 608 ] in reversing antibiotic resistance in S. aureus and/or enterococci have also been published.…”
Section: Alternative Treatment Options For Vancomycin Resistant Infec...mentioning
confidence: 87%
“…PBT2 is a safe-for-human-use zinc ionophore previously developed to treat neurodegenerative diseases, which has been shown to break resistance to multiple classes of antibiotics in a variety of animal models [ 601 , 602 , 603 , 604 ]. Bohlmann et al showed that PBT2, in the presence of zinc, is bactericidal against MRSA and VRE.…”
Section: Alternative Treatment Options For Vancomycin Resistant Infec...mentioning
confidence: 99%
“…David M. P. De Oliveira (University of Queensland, Australia) discussed the repurposing of existing drugs to combat antimicrobial resistance. , PBT2, a safe-for-human clinical drug candidate to treat Alzheimer’s disease, in combination with zinc was observed to break intrinsic Gram-positive polymyxin resistance in Streptococcus pyogenes (Group A Streptococcus; GAS), Staphylococcus aureus (including methicillin-resistant S. aureus ), and vancomycin-resistant Enterococcus faecium in vivo . , In addition, using the globally disseminated M1T1 GAS strain 5448 as a model for proof of principle, colistin in the presence of PBT2 + zinc was highlighted to be bactericidal. , Furthermore, PBT2 + zinc was observed to dysregulate GAS metal ion homeostasis, notably decreasing the cellular manganese concentrations. , Last, using a murine model of a wound infection, PBT2 + zinc and colistin was shown to be an efficacious treatment against a streptococcal skin infection. , Overall, this study provides insight into the investigation of the potential antimicrobial nature of PBT2 and next generation polymyxin antibiotics for the treatment of Gram-positive bacterial infections. , …”
Section: Daymentioning
confidence: 99%
“…Consistently, in a murine wound model of infection utilizing the polymyxin-resistant K. pneumoniae strain, a polymyxin plus PBT2 combination significantly reduced the bacterial load at the infection side [ 109 ]. Intriguingly, PBT2 plus zinc restored colistin activity in intrinsically colistin-resistant Gram-positive bacteria, including Group A Streptococcus , methicillin-resistant Staphylococcus aureus , and vancomycin-resistant Enterococcus faecium [ 112 ]. In a murine wound infection model targeting a Group A Streptococcus strain, the PBT2 plus colistin combination had a bactericidal effect [ 112 ].…”
Section: Pbt2mentioning
confidence: 99%
“…Intriguingly, PBT2 plus zinc restored colistin activity in intrinsically colistin-resistant Gram-positive bacteria, including Group A Streptococcus , methicillin-resistant Staphylococcus aureus , and vancomycin-resistant Enterococcus faecium [ 112 ]. In a murine wound infection model targeting a Group A Streptococcus strain, the PBT2 plus colistin combination had a bactericidal effect [ 112 ]. Consequently, the utility of next-generation polymyxins plus PBT2 for the treatment of resistant Gram-positive bacterial infections can be investigated in future studies.…”
Section: Pbt2mentioning
confidence: 99%